Does Investor Sentiment Predict the Near-Term Returns of the Chinese Stock Market? - Cheema, M.; Man, Y.; Szulczyk, Kenneth (Wiley-Blackwell Publishing Asia, 2018)
© 2018 International Review of Finance Ltd. Recent evidence on the relationship between investor sentiment and subsequent monthly market returns in China shows that investor sentiment is a reliable momentum predictor since an increase (decrease) in investor sentiment leads to higher (lower) future returns. However, we suggest that momentum predictability of investor sentiment originates from the boom and bust period of 2006-2008 (the bubble period hereafter). The bubble period is characterized by several months of sustained optimism followed by several months of sustained pessimism, with the market consequently earning high (low) returns following high (low) sentiment months. Therefore, we find a strong positive association between investor sentiment and subsequent market returns during the bubble period. However, investor sentiment has a negligible impact on subsequent monthly market returns once we exclude the bubble period.